Vascular expression of annexin A2 in lupus nephritis. Issue 6 (28th October 2015) - Salle, V; Cordonnier, C; Schmidt, J; Mazière, C; Smail, A; Attencourt, C; Mabille, M P; Mazière, J C; Makdassi, R; Choukroun, G; Diouf, M; Duhaut, P; et al.
Abstract : Aims: To evaluate vascular expression of annexin A2 (ANXA2) and its subunit S100A10 in lupus nephritis (LN). Methods: The present histological study included 14 patients with LN and 11 controls (patients with non-lupus kidney diseases). Kidney biopsies from patients with lupus were scored for lupus glomerulonephritis (according to the International Society of Nephrology/Renal Pathology Society 2003 classification) and vascular lesions (such as microthrombi and antiphospholipid syndrome nephropathy (APSN)). ANXA2 and S100A10 expression in glomerular and peritubular capillaries was evaluated by immunohistochemistry on tissue sections. The staining intensity score ranged from 0 (no expression) to 4 (intense expression). Results: In patients with LN, the median age (range) at first kidney biopsy was 36 (18–49). Vascular lesions were observed in six patients (including two with APSN). We observed intense expression of ANXA2 in glomerular and peritubular capillaries while expression of S100A10 was weaker. However, one of the patients with APSN showed strong S100A10 expression. Patients with LN and controls differed significantly in terms of S100A10 expression in peritubular capillaries. We also observed a statistical difference between patients who had LN with renal vascular lesions and those without renal vascular lesions in terms of ANXA2 expression in peritubular capillaries. Conclusions: The presence of vascular lesions in LN appears to be associated with significant differences in the vascular expression of ANXA2. Vascular expression of ANXA2 was somewhat higher in LN. Vascular expression of S100A10 was somewhat lower in LN (except one of the two patients with APSN). Further studies of ANXA2's putative value as a biomarker of active LN or of vascular lesions in LN are required.